2012
DOI: 10.1371/journal.pone.0040884
|View full text |Cite|
|
Sign up to set email alerts
|

To Eat or Not to Eat? Debris Selectivity by Marine Turtles

Abstract: Marine debris is a growing problem for wildlife, and has been documented to affect more than 267 species worldwide. We investigated the prevalence of marine debris ingestion in 115 sea turtles stranded in Queensland between 2006–2011, and assessed how the ingestion rates differ between species (Eretmochelys imbricata vs. Chelonia mydas) and by turtle size class (smaller oceanic feeders vs. larger benthic feeders). Concurrently, we conducted 25 beach surveys to estimate the composition of the debris present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
2
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 36 publications
(45 reference statements)
6
93
2
10
Order By: Relevance
“…We did not find a correlation between CCL and the number or mass of ingested plastic items, which is consistent with other studies (Bugoni et al, 2001;Tourinho et al, 2010;Lazar & Gračan, 2011). Although some studies have suggested that juveniles are more prone to plastic ingestion (Balazs, 1985;Bjorndal, 1997;Schuyler et al, 2012); however, we can not presume the same, since in this study only one adult animal was observed.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We did not find a correlation between CCL and the number or mass of ingested plastic items, which is consistent with other studies (Bugoni et al, 2001;Tourinho et al, 2010;Lazar & Gračan, 2011). Although some studies have suggested that juveniles are more prone to plastic ingestion (Balazs, 1985;Bjorndal, 1997;Schuyler et al, 2012); however, we can not presume the same, since in this study only one adult animal was observed.…”
Section: Discussionsupporting
confidence: 89%
“…Probably, the predominant number of Green Turtles in the present study was due to the fact this species use the coral reefs of the Paraíba coast as a feeding ground (Mascarenhas et al, 2005), favoring their stranding in the study area. Green turtles may be especially prone to plastic ingestion, since this type of debris is commonly found adhered to their main food resource, algae (Reis et al, 2010), but Schuyler et al, (2012) not found significant difference in the plastic ingestion between Green and Hawksbill species. Both species, exhibit similar feeding behavior, with smaller turtles feeding pelagically, and larger turtles shifting to benthic feeding (Bjorndal, 1997).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These characteristics have identified significant temporal change in plastic assemblages, where concentrations alone yielded no conclusive results (Shaw and Day, 1994;Vlietstra and Parga, 2002). This type-and color-dependent variability has been ascribed to predator selectivity when plastics are mistaken for food (Shaw and Day, 1994;Schuyler et al, 2012), but may also be due to type-dependent density changes and chemical degradation causing discoloration and bleaching (Pérez et al, 2010). Studies that report plastic type and colors, found the dominant proportion of SMPs in the open ocean to be white or clear in color, and composed of hard plastic fragments (Shaw and Day, 1994;Morét-Ferguson et al, 2010;Reisser et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Minchin, 1996Gregory, 2009;Majer et al, 2012;Farrapeira, 2011), enredamento de animais (Laist, 1997;Gregory, 2009), adsorção de poluentes químicos e possível transferência aos organismos (Takada, 2006;Derraik, 2002;Mato et al, 2001;Teuten, 2009;Endo et al, 2005;Rios et al, 2007;Karapanagioti, 2008;Ogata et al, 2009;Frias et al, 2010;Bond et al, 2011;Van et al,2012;Ashton et al, 2010;Holmes et al, 2012) e, também, podem ser ingeridos (Thompson, 2004;Boerger et al, 2010;Davison et al, 2011;Tourinho et al, 2010;Gregory, 2009;Graham & Thompson, 2009;Colabuono et al, 2009;Barbieri, 2009;Yamashita et al, 2011;Simmonds, 2012;Schuyler et al, 2012;Miranda, 2011 (Hall, 2000;Hammer et al, 2012), tornando-se cada vez mais escuros.…”
Section: Impactos Estéticos E Ecológicos Dos Microplásticos Ou Pelletsunclassified